Diastereoselective synthesis of arene ruthenium(II) complexes containing chiral phosphetane-based tethers - Heinemann, Frank Wilhelm; et al. (Organometallics, 2006)
Enantiomerically pure cyclic (R,R)-sulfates have been transformed into novel enantiopure ligands of the general type (S,S)-2,4-R-2-1-(3-phenylpropyl)phosphetane (7a-c; R = Cy, i-Pr, t-Bu). 7a-c split the arene ruthenium complex dimer [RuCl2(eta(6) -C6H5COOMe)(2)] (8) by forming the mononuclear sigma complexes (S-c,S-c)-[RuCl2(eta(6)-C6H5COOMe)2,4-R-2-1-(3-phenylpropyl)-eta(1)-phosphetane] (9a-c). An intramolecular arene ligand displacement reaction leads to (S-c,S-c)-[RuCl22,4-R-2-1(eta(6)-3-phenylpropyl)-eta(1)-phosphetane] (10a-c) with tethered side chains of the arene ligand. Nucleophilic substitution of a chloride ligand by aniline with the assistance of NaPF6 gives access to the diastereomeric complex salts (S-c,S-c)-[RuCl(aniline)2,4-R-2-1-(eta(6)-3-phenylpropyl)-eta(1)-phosphetane] (11a-c). Good diastereoselectivities were obtained with de values between 84 and 88%. The absolute structures of the major diastereomers of 11a-c have been determined by X-ray structure analysis. R-Ru,S-C,S-C configurations were found in all cases. DFT calculations performed on the dechlorinated 16-valence-electron intermediate cation (S-c,S-c)-[RuCl2,4-di-tert-butyl-1-(eta(6)-3-phenylpropyl)-eta(1)-phosphetane](+) ([12](+)) are in favor of an attack of aniline from the pro-R-Ru side of the complex. Investigation of the relative stabilities of the R-Ru and S-Ru diastereomers of the complex cation [11c](+) revealed an almost isoenergetic situation. The diastereoselectivity of the ligand exchange reaction is therefore believed to be kinetically controlled.